2019
DOI: 10.15625/0868-3166/29/4/14178
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Sudan dye at low concentrations by surface-enhanced Raman spectroscopy using silver nanoparticles

Abstract: Sudan dyes are red colorants banned from use for food due to their toxic properties. However, because of the cheapness, they are sometimes adulterated into food illegally. Currently surface-enhanced Raman spectroscopy (SERS) is emerging as a good method to detect residues (including trace amounts) of Sudan dyes in food. In this report we present the SERS detection of Sudan I (a type of Sudan dyes) to concentrations as low as 1 ppb, using a very simple SERS substrate, which is made from silver nanoparticles che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The first target of detection is organic dyes, because the SERS technique is extremely sensitive to them. For example with AgNFs/Si SERS substrate we have detected crystal violet down to a concentration of 0.01 ppm [27], while with AgNPs/Si substrate, sudan I with concentrations as low as 1 ppb has been detected [18]. The next detection target is pesticides and other toxic substances.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The first target of detection is organic dyes, because the SERS technique is extremely sensitive to them. For example with AgNFs/Si SERS substrate we have detected crystal violet down to a concentration of 0.01 ppm [27], while with AgNPs/Si substrate, sudan I with concentrations as low as 1 ppb has been detected [18]. The next detection target is pesticides and other toxic substances.…”
Section: Resultsmentioning
confidence: 97%
“…In order to fabricate AgNDs on Si (AgNDs/Si), the most important thing is to change the ratio of HF/AgNO 3 accordingly. Both chemical and electrochemical deposition can yield Ag-NDs/Si, however electrochemical deposition will give AgNDs with better branching [18]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Sudan dyes at low concentration can be identified by surface-enhanced Raman scattering (SERS) [ 20 ]. However, most studies using SERS to analyze Sudan dyes have only focused on Sudan I, or have evaluated the enhancement effects of a substrate on standard Sudan dye solutions [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%